Legal and Technical Analysis of Overlapping Titles in Baguio City - ENGR. CHARLIE M. FELIX; ENGR. CRISELDA S. FELIX, PhD; KURT MANUEL ARGUEZA; JACKSON BUCAGAN; ESCELJOY GUILANDA; HENSHAFIR YONA LAWAGAN; KENJI CATE TIO (Future Science / FSH-PH Publications, 2026)
This study aims to analyze the legal and technical problems involving overlapping land titles in Baguio City. The study was conducted at different households, firms and the DENR Regional Office located at Baguio City with a total of 19 participants consisting of landowners, geodetic engineers and DENR employees. The study employed qualitative research design with the use of one on one interview as the primary instrument in gathering data. All gathered data were summarized, analyzed, coded, themed and interpreted with the use of thematic analysis. Based on the data, these are the following findings: the causes of overlapping are contradiction of reference system, precision and accuracy of old and new practices, lack of inter-agency coordination, inaccessibility of old records, and human error; landowners, geodetic engineers and DENR employees have contributions to overlapping; the possible approach to overlapping are unification of reference system, improvement of inter-agency coordination and Joint Relocation survey. The conclusions are the following: the evolution of survey is one of the main factor of overlapping, from the instrument, practices, methods and systems used; every stakeholders holds a responsibility in having overlapping land titles whether that be intentional or unintentional; having one system is the ideal solution to overlapping and its proper implementation should be strictly overlooked.